Evaluation of the gastrointestinal tract in mdx mice: an experimental model of Duchenne muscular dystrophy. Issue 8 (29th July 2018) - Feder, David; Ierardi, Mariana; Covre, Ana Laura; Petri, Giuliana; Carvalho, Alzira Alves de Siqueira; Fonseca, Fernando Luiz Affonso; Bertassoli, Bruno Machado
Abstract : This study describes the functional and morphological alterations in the intestines of mdx mice (n = 4) compared with the intestinal features of C57BL/10 mice (n = 7) at 2 months of age. The whole gut transit time (carmine red) and the upper gut transit time (activated charcoal) were measured, and light microscopy was utilized to view stained sections (H&E and picrosirius red) for histological analysis. No significant difference in mean evacuation time for the whole gut was observed between the two groups, but a significant delay in activated charcoal passage was observed in the mdx mice. Visually, a higher concentration of collagen fibers in the submucosal region was apparent in the mdx mice. The concentration of collagen fibers in the stomach and small intestine suggests a direct relationship with the decrease in motility of the upper gastrointestinal tract in the mdx mice. Further experimental studies should be conducted to develop therapeutic alternatives to collagen inhibition to control these manifestations.